2022
DOI: 10.1126/scitranslmed.abi8633
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell profiling of environmental enteropathy reveals signatures of epithelial remodeling and immune activation

Abstract: Environmental enteropathy (EE) is a subclinical condition of the small intestine that is highly prevalent in low- and middle-income countries. It is thought to be a key contributing factor to childhood malnutrition, growth stunting, and diminished oral vaccine responses. Although EE has been shown to be the by-product of a recurrent enteric infection, its full pathophysiology remains unclear. Here, we mapped the cellular and molecular correlates of EE by performing high-throughput, single-cell RNA-sequencing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 67 publications
2
9
0
Order By: Relevance
“… 5 , 20 For example, inflammatory diseases such as inflammatory bowel disease (IBD) are associated with certain antimicrobial genes like DUOX2 and DUOXA2, and elevated DUOX2 levels in the intestine often indicate increased inflammation and mucosal dysbiosis. 21 , 22 We observed that exposure to ND in healthy donors did not dramatically alter to the expression of these genes. This is interesting because it may indicate that short-term malnutrition might not be sufficient to induce significant changes in those genes compared to chronic conditions like those observed in EED and IBD patients.…”
Section: Discussionmentioning
confidence: 65%
“… 5 , 20 For example, inflammatory diseases such as inflammatory bowel disease (IBD) are associated with certain antimicrobial genes like DUOX2 and DUOXA2, and elevated DUOX2 levels in the intestine often indicate increased inflammation and mucosal dysbiosis. 21 , 22 We observed that exposure to ND in healthy donors did not dramatically alter to the expression of these genes. This is interesting because it may indicate that short-term malnutrition might not be sufficient to induce significant changes in those genes compared to chronic conditions like those observed in EED and IBD patients.…”
Section: Discussionmentioning
confidence: 65%
“…Underlying this issue is our previously limited understanding of the pathophysiology of this condition, which has been expanding by leaps and bounds in the last decade. Recent work has highlighted in both pre-clinical studies and clinical trials the potential value of amino acid supplementation 18,19,21,27 , and the potentially core contribution of deficient animal protein intake, and our work demonstrates that this is highly likely to be a major contributing factor in EE and the stunting syndrome.…”
Section: Discussionmentioning
confidence: 65%
“…Mechanistic work attempting to recapitulate the EE phenotype has also noted a requirement for protein/amino acid deficiency: both murine and gut-on-a-chip culture work demonstrate that deficiency in amino acids, especially tryptophan, is necessary to generate the appropriate phenotype 17,18 . Translational work looking at adults with EE have similar findings: a recent study using single cell RNA sequencing of Zambian adults with EE noted deficiency of tryptophan, which as a precursor of serotonin and a modulator of indolamine 2-3 dioxygenase (IDO), a substantial immune activity and epithelial regulator, whose activity as documented by kynurenine/tryptophan ratio is directly associated with growth outcomes [19][20][21][22][23][24][25][26] . The aggregate evidence suggests a key mechanistic component of EE disease formation may be driven or reflected by absence of animal protein intake with resulting amino acid deficiency, particularly tryptophan deficiency.…”
mentioning
confidence: 88%
“…EECs are part of a population of rarer cell types that play crucial roles in tissue maintenance but cannot always be detected by bulk RNA sequencing as they only make up 1% of all epithelial cells. Single cell transcriptomics may be a better way of detecting the presence of such rarefied gene transcripts (Kummerlowe et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%